Fewer species of Argosarchus and Clitarchus stick insects (Phasmida, Phasmatinae): evidence from nuclear and mitochondrial DNA sequence data - Steven A. Trewick; Julia Goldberg; Mary Morgan‐Richards (Zoologica Scripta, 2005)
The systematics of three genera of New Zealand stick insect in the subfamily Phasmatinae were investigated in light of inconsistencies in morphological variability within and among species. We sequenced a region of the mitochondrial genome, cytochrome oxidase (COI & COII; 1448 bp), and a nuclear marker, the internal transcribed spacers (ITS1 & ITS2; 1804 bp) from 49 stick insects. Mitochondrial DNA sequence divergences among the three genera ( Argosarchus , Clitarchus and Acanthoxyla ) were relatively high (∼12%) but the current taxonomy within genera was not supported. Within the three genera, low levels of genetic divergence were observed at both nuclear and mitochondrial loci, and phylogenetic analyses failed to support reciprocal monophyly of the two species in Argosarchus and Clitarchus . Sympatric individuals of Argosarchus spiniger and A. horridus were more closely related to each other than to members of their respective morphospecies from elsewhere. No males were found in the Chatham Island population of Argosarchus and although this population has been referred to as A. schauinslandi , genetic and morphological evidence does not support its distinction from mainland Argosarchus . Likewise, individuals identified as Clitarchus tuberculatus were genetically identical, or most similar to, C. hookeri from the same or adjacent sites rather then grouping with the stick insects they were morphologically most similar to. Lack of spatial, behavioural or ecological evidence concordant with the described species A. spiniger , A. schauinslandi and C. tuberculatus leads us to infer that these species are synonymies of A. horridus and C. hookeri respectively. We conclude that Argosarchus and Clitarchus have each been over‐split and actually consist of a single morphologically polymorphic, facultative parthenogenetic species. The genus Acanthoxyla with eight described species also has low levels of genetic divergence, similar to those found in Argosarchus and Clitarchus . A possible hybrid origin of Acanthoxyla involving its sister genus Clitarchus is implied by sharing of ITS sequence variants, but further sampling is needed before the species status of these obligate parthenogenetic lineages can be resolved. In contrast to some New Zealand Orthoptera, the Phasmatinae show little genetic variation suggesting coalescence in recent times, possibly reflecting lineage sorting in the Pleistocene.

Hybrid origin of a parthenogenetic genus? - MARY MORGAN‐RICHARDS; STEVEN A. TREWICK (Molecular Ecology, 2005)
The origin of the obligate‐parthenogenetic New Zealand stick insect genus Acanthoxyla was investigated using cytogenetics and sequencing of nuclear and mitochondrial DNA. Little mitochondrial DNA sequence variation (COI‐II) was found among seven species of the genus Acanthoxyla and we found no evidence for monophyly of the morphologically distinguished lineages. In contrast, two distinct clades of nuclear sequence (ITS) were obtained, one is restricted to the genus Acanthoxyla , while the other includes sequences obtained from its sister genus Clitarchus . Although Acanthoxyla appears to be diploid (2n = 36–38), it has two ill‐matched chromosome pairs. We hypothesize that two or more hybridization events involving the parental sexual species Clitarchus hookeri and an unknown taxon probably resulted in the formation of the parthenogenetic genus Acanthoxyla. However, the karyotype of Acanthoxyla bears little resemblance to the karyotype of the putative paternal species C. hookeri so the exact nature of Acanthoxyla remains in question.

After the deluge: mitochondrial DNA indicates Miocene radiation and Pliocene adaptation of tree and giant weta (Orthoptera: Anostostomatidae) - Steven A. Trewick; Mary Morgan‐Richards (Journal of Biogeography, 2005)
Aim New Zealand broke away from the margins of Gondwana c . 75 Ma. Since then, New Zealand taxa derived from the Gondwanan biota are thought to have been exposed first to a subtropical climate on a low lying terrain, then severe land reduction during the Oligocene marine transgression, followed by much cooler climates of the Pliocene and Pleistocene, at which time mountain ranges emerged. The biological consequence of New Zealand's geological and climatic history is not well understood, in particular the extent to which the Oligocene acted as a biological bottleneck remains unresolved. Methods We used mitochondrial cytochrome oxidase I and 12S DNA sequences to examine the extent of diversity and inferred timing of speciation of New Zealand weta (Anostostomatidae), a group of Orthoptera with a Gondwanan distribution generally thought to be ancient inhabitants of New Zealand. Main conclusions We hypothesize that at least three distinct groups of weta survived the Oligocene marine transgression and radiated subsequently. Speciation followed during the Miocene and radiation into new habitats occurred during the Pliocene when mountain building created novel environments. Patterns of genetic diversity within species reflect, in some instances, geographical subdivision in the Pliocene, and in other cases, Pleistocene range changes resulting from climate change.